Analisis Tindak Tutur Perlokusi terhadap Kritik Sosial melalui Humor Gelap dalam Video Youtube Somasi: Kajian Pragmatik - Mulyo Kurniati (Program Studi Tadris Bahasa Indonesia Universitas Islam Tribakti Lirboyo Kediri, 2025)
The popularity of digital media such as YouTube has made it an effective platform for delivering social criticism through entertainment content. One example is the program